2011
DOI: 10.1016/j.jneumeth.2011.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and extra-cranial effects of transient blood pressure changes on brain near-infrared spectroscopy (NIRS) measurements

Abstract: Highlights► We recorded NIRS from the visual cortex during pattern-reversal stimulation. ► Transient blood pressure changes were induced by arm-raising. ► Blood pressure changes significantly altered deep and shallow NIRS recordings. ► The effect appears to originate from both intra- and extra-cranial regions. ► Blood pressure must be considered as a potential confound in NIRS studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 26 publications
(22 reference statements)
4
58
0
1
Order By: Relevance
“…Task execution may also lead to significant changes in BP during certain experimental tasks such as arm-rising (Minati et al, 2011), anagram task (Tachtsidis et al, 2008a(Tachtsidis et al, ,c, 2009), word generation and constructional puzzle task (Moody et al, 2005), semantic continuous performance task (Jelzow et al, 2011), or emotional picture presentation (Minati et al, 2009). These BP changes affect hemodynamics in the extracerebral compartment, measured as stimulus/task-related changes in SBF and/or volume (SBV) (Kirilina et al, 2012;Takahashi et al, 2011), or even in the cerebral compartment itself (Minati et al, 2011 Another source of systemic component is the influence of the autonomic nervous system (ANS) on the cerebral vasculature (Hamel, 2006;Wahl and Schilling, 1993). For example, Giller et al (2000) showed that a rhythmic handgrip exercise causes a sympathetic-mediated modulation of the hemodynamics in the middle cerebral artery.…”
Section: Classification Of Signal Componentsmentioning
confidence: 99%
“…Task execution may also lead to significant changes in BP during certain experimental tasks such as arm-rising (Minati et al, 2011), anagram task (Tachtsidis et al, 2008a(Tachtsidis et al, ,c, 2009), word generation and constructional puzzle task (Moody et al, 2005), semantic continuous performance task (Jelzow et al, 2011), or emotional picture presentation (Minati et al, 2009). These BP changes affect hemodynamics in the extracerebral compartment, measured as stimulus/task-related changes in SBF and/or volume (SBV) (Kirilina et al, 2012;Takahashi et al, 2011), or even in the cerebral compartment itself (Minati et al, 2011 Another source of systemic component is the influence of the autonomic nervous system (ANS) on the cerebral vasculature (Hamel, 2006;Wahl and Schilling, 1993). For example, Giller et al (2000) showed that a rhythmic handgrip exercise causes a sympathetic-mediated modulation of the hemodynamics in the middle cerebral artery.…”
Section: Classification Of Signal Componentsmentioning
confidence: 99%
“…Task-evoked change in mean arterial blood pressure (ΔMAP) has been demonstrated for a number of different experimental fNIRS protocols, e.g., arm-raising (ΔMAP ≈ 6 mm Hg), 9 visual stimulation (ΔMAP ≈ 2 mm Hg), 10 anagram solving (ΔMAP ≈ 3 to 5 mm Hg, 11,12 6 to 7 mm Hg), 13 or hypercapnia (ΔMAP ≈ 4 mm Hg), 14 hypocapnia (ΔMAP ≈ 4.5 mm Hg;…”
Section: What Factors Cause False Positives Andmentioning
confidence: 99%
“…Therefore NIRS measurements reflect changes in cortical hemodynamics, only. More importantly, NIRS signals contain extra-cortical contributions from shallower tissues (e.g., scalp) (Minati et al, 2011;Obrig et al, 2000;Oscillators, 2010;Tachtsidis et al, 2008). Superficial layers account for most of the NIRS signal, and removal of such contamination can be difficult, although possible (Gagnon et al, 2014(Gagnon et al, , 2012.…”
Section: Discussionmentioning
confidence: 99%